Entre as minas e os recôncavos: a administração da Capitania do Espírito Santo na primeira metade do século XVIII (1718-1744) - Fernandez, Felipe de Souza (2023)
The governance of the Captaincy of Espírito Santo in the first half of the 18th century was diverse, given the contingencies faced by the Portuguese Crown in competition with other emerging European states or by the demands of the inhabitants of this Captaincy, particularly those from the town of Vitória. Thus, the study explores the years from 1718, when the Crown incorporates the Captaincy of Espírito Santo, to the end of the demarcation of the district of the Ouvidoria do Espírito Santo in 1744, created in 1732. The process of territorialization of the Captaincy of Espírito Santo in Portuguese America is analyzed, highlighting its importance in defending the Center-South of Portuguese America and its economic and demographic growth, with the expansion and territorial occupation by the colonizers. In this proposed analysis, key points in the Crown's administration are observed, such as in 1722 when it is divided in the legal and administrative political sphere by royal decree, with Espírito Santo being subordinated to Rio de Janeiro and Bahia, respectively. Through exchanges of information (letters, requests) from royal agents, including the Captains and the Governors General of the State of Brazil, this space was shaped to appease the disturbances of the "republic," that is, to maintain the "common good" of the Captaincy, a primary function of the Portuguese Monarchy in the Modern Age. These conflicts are researched mainly through documents that show the interests of the local colonial elites - inhabitants, royal officials of the town of Vitória - as well as the specificity of the power of the Society of Jesus in the economic and political control rooted in the territory. Finally, a specific study is dedicated to the trajectory and creation of the district of the Captaincy of Espírito Santo through its first General Ombudsman, Pascoal Ferreira de Veras.